2003
DOI: 10.1007/s00439-003-0916-6
|View full text |Cite
|
Sign up to set email alerts
|

Linkage analysis of prostate cancer susceptibility: confirmation of linkage at 8p22–23

Abstract: Frequent loss of heterogeneity in prostate cancer cells and linkage studies of families affected by hereditary prostate cancer (HPC) have implied that the short arm of chromosome 8, specifically 8p22-23, may harbor a prostate-cancer-susceptibility gene. In a recent study, seven potentially important mutations in the macrophage scavenger receptor 1 gene (MSR1), located at 8p22, were observed in families affected with HPC, and an indication of co-segregation between these mutations and prostate cancer was report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…However other than a replication by the group describing the initial results on chromosome 20, none of these peaks coincided precisely with any of the previously reported linkage peaks. The most promising were the results on chromosome 19 by Wiklund et al (24) which is close to the peak on chromosome 19 originally reported by reported by Hsieh et al (27).…”
Section: Loci Mapped To Datesupporting
confidence: 75%
“…However other than a replication by the group describing the initial results on chromosome 20, none of these peaks coincided precisely with any of the previously reported linkage peaks. The most promising were the results on chromosome 19 by Wiklund et al (24) which is close to the peak on chromosome 19 originally reported by reported by Hsieh et al (27).…”
Section: Loci Mapped To Datesupporting
confidence: 75%
“…Bostwick et al detected loss of 8p21–12 in 37% of PIN foci and in 46% of cancer foci. In a recent study, 7 potentially important mutations in the macrophage scavenger receptor 1 gene (MSR1), located at 8p22, were observed in families affected with prostate cancer, and an indication of cosegregation between these mutations and prostate cancer was reported 1297. These findings suggest that more than 1 tumor suppressor gene may be located on 8p, and inactivation of these tumor suppressor genes may be important for the initiation of prostate cancer.…”
Section: 0 Goalsmentioning
confidence: 97%
“…In addition to its linkage to hereditary CaP, the macrophage receptor scavenger 1 ( MSR1 ) gene is located at a locus (8p22) that is often deleted in prostate tumors [ 118 , 119 ]. MSR1 mutations have been associated with CaP risk in both hereditary and sporadic CaP among Caucasian and AA men [ 98 ].…”
Section: Germline Mutations Associated With Hereditary Prostate Camentioning
confidence: 99%